Avaliação histológica da pele após exposição a gel acrescido de hialuronidase associado ou não a ultra-som - Chorilli, Marlus [UNESP]; Zague, Vivian; Ribeiro, Maria Cristina de Almeida Prado; Leonardi, Gislaine Ricci; Pires-De-Campos, Maria Sílvia Mariani; Polacow, Maria Luiza Ozores (My University, 2007)
The objective of this work was to verify the effect in the skin of male swines gel (G) containing hyaluronidase (H) associated or not to ultrasound (US). In different areas was applied G; G+US; G+H; G+H+US and mesotherapy (M). Skin fragment was processed in paraffin. To evidence hyaluronic acid (HA) coloration with Alcian Blue (AB) was used and coloration with Hematoxilin/Eosin for morphometry. It was observed that G+H and G+H+US did not reduce coloration for the AB nor presented significant differences for the morphometry. When H was applied mesoteraphycally coloration for the AB diminished. Then, the use of H associated or with US did not seem efficient in the HA reduction.
Histological evaluation of the skin after exposition to the gel increased of hyaluronidase associated or not to ultrasound
Keywords: Histochemical; Hyaluronidase; Morphometry; Ultrasound; alcian blue; eosin; hematoxylin; hyaluronic acid; hyaluronidase; animal tissue; controlled study; gel; histology; male; morphometrics; nonhuman; skin examination; swine; ultrasound